2024
DOI: 10.1038/s41467-023-44450-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of printed nanostructured networks using high-resolution 3D FIB-SEM nanotomography

Cian Gabbett,
Luke Doolan,
Kevin Synnatschke
et al.

Abstract: Networks of solution-processed nanomaterials are becoming increasingly important across applications in electronics, sensing and energy storage/generation. Although the physical properties of these devices are often completely dominated by network morphology, the network structure itself remains difficult to interrogate. Here, we utilise focused ion beam – scanning electron microscopy nanotomography (FIB-SEM-NT) to quantitatively characterise the morphology of printed nanostructured networks and their devices … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…We demonstrate this impedance approach using liquid-deposited networks of electrochemically exfoliated MoS 2 nanosheets ( l NS ≈ 1 μm, t NS ≈ 3.3 nm) with low porosity 47 and large-area junctions 19 (Fig. 4a ).…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…We demonstrate this impedance approach using liquid-deposited networks of electrochemically exfoliated MoS 2 nanosheets ( l NS ≈ 1 μm, t NS ≈ 3.3 nm) with low porosity 47 and large-area junctions 19 (Fig. 4a ).…”
Section: Resultsmentioning
confidence: 84%
“…Nanosheet aspect ratio, k NS , and AgNW diameter, D NW , were measured using AFM and SEM respectively. Network porosity, P Net , values were taken from Gabbett et al 47 and Carey et al 19 . WS 2 and WSe 2 nanosheet mobilities were extracted from Kelly et al 53 , while the mobility of graphene was taken as the in-plane mobility of graphite 83 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is not known how exactly this re-stacking occurs or how it depends on the thickness of the sheets, the fact that thicker sheets tend to be stiffer makes it reasonable to think that they will re-stack worse than the thinner ones and, therefore, tend to lose less area with respect to the case without re-stacking. Indeed, there are previous instances in the literature where a thinner, electrochemically exfoliated 2D material (e.g., graphene) is shown to lead to more compact, less porous re-stacked films than its thicker, liquid-phase exfoliated counterpart [45]. (g) Typical Raman spectra of the starting bulk MoS 2 bulk crystal (black trace) and cathodically exfoliated MoS 2 (green trace).…”
Section: Physicochemical Characterization Of the Cathodically Exfolia...mentioning
confidence: 99%
“…Such nanoparticle diffusion of AgNPs coatings on the GNP layer was recently proven by 3D FIB-SEM observations. 36 It has been reported that this increment in sheet resistance can be caused by blocking the conductive path in the coated material on polymer substrates created by the polymer lubrication effect. 37 Another reason is that polymers retain water molecules on the sensing layer by the low contact angle of the polymers.…”
Section: Characterization Of Strain Sensormentioning
confidence: 99%